The Impact of Leadership, Work Discipline, and Employee Empowerment on Employee Performance in Enhancing Economic Efficiency at the Social Services Office of Buleleng Regency - Susanta, Gede Nova (International Journal of Economics Development Research (IJEDR), 2025)
This research aims to examine how leadership, work discipline, and employee empowerment influence employee performance at the Social Services Office of Buleleng Regency, particularly in the context of improving economic efficiency in public service delivery. Data was collected using a questionnaire method, with analysis conducted through various statistical techniques including multiple linear regression. The findings indicate that leadership, work discipline, and empowerment each have a positive and significant impact on employee performance, both individually and collectively. These factors play a critical role in enhancing organizational productivity, which is essential for achieving better economic outcomes in public sector institutions. Strengthening these internal factors can thus contribute to more efficient service delivery and optimal resource utilization within government agencies.